2020
DOI: 10.1002/jper.20-0360
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of poly lactic‐co‐glycolic acid‐coated β‐tricalcium phosphate for alveolar ridge preservation: A multicenter randomized controlled trial

Abstract: Background Alveolar ridge preservation via socket grafting (ARP‐SG) is indicated to attenuate physiologic alveolar bone resorption as a consequence of tooth extraction. However, a specific bone grafting material that is patently superior has not been identified yet. The aim of this randomized controlled trial was to evaluate the efficacy of a moldable alloplastic graft, Poly Lactic‐Co‐Glycolic Acid‐Coated β‐Tricalcium Phosphate (PLGA‐β‐TCP), for ARP purposes [Group A] compared to freeze‐dried bone allograft (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 37 publications
2
34
0
Order By: Relevance
“…Therefore, to avoid underestimation of the effect of ARP, we evaluated only the effect of ARP at the posterior teeth. Meanwhile, increasing studies found that alveolar ridge preservation at posterior teeth with an intact alveolar socket [40] or non-molar and molar teeth with non-intact alveolar sockets [41] could observe significantly reduced requirement for bone augmentation at implant placement. This study has some limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, to avoid underestimation of the effect of ARP, we evaluated only the effect of ARP at the posterior teeth. Meanwhile, increasing studies found that alveolar ridge preservation at posterior teeth with an intact alveolar socket [40] or non-molar and molar teeth with non-intact alveolar sockets [41] could observe significantly reduced requirement for bone augmentation at implant placement. This study has some limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Tooth extraction inevitably leads to a variable degree of alveolar ridge atrophy 1–3 . Among other interceptive therapies, 4,5 contemporary evidence strongly supports the effectiveness of alveolar ridge preservation (ARP) therapy to prevent extensive alveolar ridge resorption after tooth extraction compared with unassisted socket healing (USH), 6,7 whether immediate implant placement is simultaneously performed or not 8 …”
Section: Introductionmentioning
confidence: 99%
“…Tooth extraction inevitably leads to a variable degree of alveolar ridge atrophy. [1][2][3] Among other interceptive therapies, 4,5 contemporary evidence strongly supports the effectiveness of alveolar ridge preservation (ARP) therapy to prevent extensive alveolar ridge resorption after tooth extraction compared with unassisted socket healing (USH), 6,7 whether immediate implant placement is simultaneously performed or not. 8 A systematic review and meta-analysis evaluating the efficacy of different ARP modalities, concluded that ARP via socket grafting as compared with tooth extraction alone, prevents horizontal (1.99 mm), vertical midbuccal (1.72 mm) and vertical mid-lingual (1.16 mm) bone resorption.…”
Section: Introductionmentioning
confidence: 99%
“…β-TCP is a biocompatible material that is of particular interest for various clinical applications as it can be synthesized with consistent batch quality because it has well-defined properties [ 15 ]. In the last two decades, their use in dentistry has increased and β-TCP has shown its efficacy in many applications, especially in the vital pulp therapy as a direct pulp-capping agent [ 16 , 17 ], in treating periodontal infra-bony defects [ 18 ], and in alveolar ridge preservation for implant placement [ 19 ]. Schiroky et al formerly incorporated TCP nanoparticles in their experimental adhesive (EA) and reported higher Knoop hardness and polymerization rate as compared with the controls [ 13 ].…”
Section: Introductionmentioning
confidence: 99%